Desenvolvimento e produção de uma vacina quimérica multi-peptídica e avaliação de sua eficácia vacinal contra ascaridíase - Ana Clara Gazzinelli Guimarães (2021)
Human ascariasis is one of the most prevalent neglected tropical diseases in the world, affecting about 450 million people, mainly school children (SAC) in developing countries. Control of human ascariasis is predominantly based on mass drug administration programs but high rates of reinfection are commonly observed. The development of a vaccine that promotes quality of life, lower morbidity and long-term protection, something not yet commercially available, would be desirable for infection control. Previously our group demonstrated that immunization with crude antigens of Ascaris sp. in mice induced an IgG-mediated protective response and a reduction of up to 60% in the number of parasites. Thus, the present study aimed to identify and characterize B-cell epitopes of Ascaris sp., as well as other parasites helminths of public health importance and to evaluate its implications in the efficacy of the vaccine. For this, two different methods were used to search for a vaccine: 1selection of target B-cell epitopes selected by data mining by a bioinformatics pipeline, as well as 2use of the Phage Display technique with the objective of identifying conformational epitopes that are recognized by specific antibodies of Ascaris sp. After the process of identification of these peptides, selection and validation by evaluating the specific reactivity of these peptides using serum from control mice, immunized with Ascaris sp. antigens, or of animals infected three times with eggs of A. suum (hyperimmune sera), the selected peptides highly specific and reactive to anti-IgG of A. suum were aligned in their best conformation and synthesized in a cloning vector for further expression and purification of polypeptide chimera. After vaccination and subsequent challenge infection in BALB/c mice, it was possible to observe a significant reduction of approximately 50% of the parasitic burden in animals immunized with ASCVac-1+MPLA chimera compared to the control group. In addition, high serum levels of vaccine-specific IgG and its subclasses IgG1, IgG3 and IgG2a were observed in the group vaccinated with chimera. Vaccination demonstrated a polarization of the Th2 response, with significant production of IL-4, IL-5, IL-13 cytokines and a regulation of IL-33 production. In addition, vaccination led to less inflammation when the profile of inflammatory cells present in BAL after vaccination + infection was observed in addition to less tissue damage when a score of total inflammation and dysfunction of the lung of the animals was evaluated. In conclusion, it was possible to observe that ASCVac-1 chimera, in addition to protecting in relation to the parasitic burden, induced a robust vaccine-specific humoral response and did not induce the production and sensitization of animals by IgE, thus becoming a potential vaccine candidate against ascariasis.